Organics alleviate the inhibition of sulfate on ANAMMOX sludge. Issue 6 (12th May 2022) - Wei, Denghui; Zhang, Xiaojing; Zhang, Shengnan; Dai, Jiaqian; Du, Jianghui; He, Yu; Wen, Xiaoyu
Abstract: Anaerobic ammonium oxidation (Anammox) was an innovative process for nitrogen removal. In this study, the influence of sulfate in different concentrations (100, 200, 300, and 400 mg L −1 ) on Anammox process were investigated in nine identical sequential batch reactors, four of which were extra supplied for organics, to study the combined effect. The results indicated the obvious inhibition by sulfate which decreased the total nitrogen removal efficiency (TNRE) to 84.1%, 81.2%, 81.2%, and 72.5%, from the control results as 91.9%. Whereas, the organics addition alleviated the inhibitory effect, through consuming the oxygen in influent, promoting the secretion of protein, and inducing the denitrifying bacteria, for which the sulfate only slightly decreased the TNRE to 89.0%, 83.7%, 83.6%, and 75.7%, respectively. Candidatus Kuenenia and Denitratisoma could coexist in Anammox system and cooperatively contribute to the nitrogen removal, when treating the nitrogenous wastewater contains both sulfate and organics.